Мистецтво та художній процес Кременеччини 1920-30-х років: предмет наукового дослідження - Панфілова, О. (Інститут народознавства НАН України, 2007)
Kremenechyna is known for its Lyceum founded in the 19th century. Its art life in the 20th century is practically unknown. Bat this unique centre of culture needs more profound studying.